2000
DOI: 10.1161/01.cir.102.15.1814
|View full text |Cite
|
Sign up to set email alerts
|

Both β 2 - and β 1 -Adrenergic Receptors Mediate Hastened Relaxation and Phosphorylation of Phospholamban and Troponin I in Ventricular Myocardium of Fallot Infants, Consistent With Selective Coupling of β 2 -Adrenergic Receptors to G s -Protein

Abstract: Despite their low density, beta(2)-adrenergic receptors are nearly as effective as beta(1)-adrenergic receptors of infant Fallot ventricle in enhancing contraction, relaxation, and phosphorylation of phospholamban and troponin I, consistent with selective coupling to G(s)-protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 26 publications
4
54
0
Order By: Relevance
“…In cardiomyocytes, the extrusion and sequestration of free calcium during diastole is dependent on cyclic AMP, is modulated by b-receptors, and is influenced by several ion transport mechanisms including the Na + /H + exchanger. [30][31][32][33][34][35][36] Cardiac b-receptors couple to a G-protein-stimulated adenylcyclase, which in turn stimulates cyclic AMP-dependent regulatory mechanisms. 30,31,33,37 Recent studies in rodent cardiomyocytes revealed that b 2 -receptors couple to G-proteins, which lead to inhibition of cyclic AMP formation downstream.…”
Section: Discussionmentioning
confidence: 99%
“…In cardiomyocytes, the extrusion and sequestration of free calcium during diastole is dependent on cyclic AMP, is modulated by b-receptors, and is influenced by several ion transport mechanisms including the Na + /H + exchanger. [30][31][32][33][34][35][36] Cardiac b-receptors couple to a G-protein-stimulated adenylcyclase, which in turn stimulates cyclic AMP-dependent regulatory mechanisms. 30,31,33,37 Recent studies in rodent cardiomyocytes revealed that b 2 -receptors couple to G-proteins, which lead to inhibition of cyclic AMP formation downstream.…”
Section: Discussionmentioning
confidence: 99%
“…Two groups found only ␤ 1 -induced troponin I phosphorylation in rats, 54,55 whereas others described phosphorylation via both subtypes in human heart. 56 Phospholamban phosphorylation has been reported after ␤ 1 -but not ␤ 2 -receptor activation in canine and human cardiomyocytes, 54,57 while in other studies, particularly in human heart, both subtypes caused phosphorylation. 55,56 ␤ 1 -Receptor stimulation increased PKA activity in the particulate fraction of cardiomyocytes, whereas after ␤ 2 -receptor stimulation this increase was limited to the soluble fraction.…”
Section: Compartmentation Of ␤-Adrenergic Signalingmentioning
confidence: 91%
“…Suggested explanations for the compartmentation in rodents include localization of b2-adrenoceptors inside caveolae in cardiomyocytes or coupling of b2-adrenoceptors to Gi-dependent pathways, acting as negative regulators of contractility (Jo et al, 2002;Xiang et al, 2002;Pavoine and Defer, 2005). The stimulation of b1-adrenoceptors hastens the relaxation (lusitropic response, LR) along with increasing the contraction (PIR) while b2-adrenoceptor stimulation has been found to evoke a PIR with no LR in cardiac tissue from rodents, cat and sheep (Xiao et al, 1999), but not human (Kaumann et al, 1999;Molenaar et al, 2000; and canine hearts (Xiao et al, 1999). In accordance with the suggestion that Gi is able to compartmentalize downstream b2-adrenoceptor signalling, inhibition of Gi by Pertussis toxin disclosed an LR to b2-adrenoceptor stimulation along with increased phosphorylation of phospholamban .…”
Section: Introductionmentioning
confidence: 99%